Salinity and temperature effects on productivity of a tropical calanoid copepod Pseudodiaptomus incisus. (15th June 2020) - Nguyen, Thuy T.; Le, Minh‐Hoang; Doan, Nam X.; Nguyen, Sy T.; Truong, Trinh S. H.; Vu, Minh T. T.; Dinh, Khuong V.
Abstract: Pseudodiaptomus species are major live feeds for the early stages of economically important marine fish in hatcheries in the South China Sea. However, we know little about the combined effects of multiple environmental parameters such as salinity and temperature on copepod productivity. To address the issue, we cultured a tropical coastal copepod Pseudodiaptomus incisus in one of 24 combinations of 8 salinities (5, 10, 15, 20, 25, 30, 35 and 40 ppt) and 3 temperatures (26, 30 and 34°C). We determined development, biomass of all stages, fecundity, percentage of females with hatched eggs and 30 hr nauplii production. Overall, the biomass, fecundity and nauplii production of P. incisus were highest at the salinity of 15–20 ppt, especially at 26°C. P. incisus showed a lower performance at both lower and higher salinities. Elevated temperatures resulted in faster development, but lower biomass, fecundity and nauplii production. Especially, nauplii production was reduced by 74% at 35–40 ppt and 34°C compared to at 15–20 ppt and 26°C. Our study provides essential information for optimizing the biomass culture of P. incisus .